Relasionalitas Dialogal Jembatan untuk Membangun Komunikasi di Tengah Pluralitas Agama Masyarakat Indonesia: Dialogue Relationality Bridges to Building Communication Amidst the Religious Plurality of Indonesian Society - Ronaldo, Paskalis; Riyanto, F.X.Eko Armada (Jurnal Filsafat Indonesia, 2025)
Indonesia is known as a country with high religious diversity. This religious diversity is one of the cultural riches of the Indonesian nation that must be maintained and preserved. Armada Riyanto, offers a philosophical view that emphasizes the importance of relationality to bridge gaps and build connections in a pluralistic society. This article explores the concept of dialogical relationality and examines Armada Riyanto's perspective on its role in promoting harmony and cooperation amid religious diversity in Indonesia. The writing of this article uses the philosophical hermeneutic method with the analysis technique used in writing this article, namely literature studies or literature that prioritizes the inductive method in its writing. The sources used come from library data, so the writing of this article is a form of library research. The author's purpose in discussing the theme of dialogal relationality in this article is to show that differences in the life of Indonesian society can be bridged with the dialog of understanding differences can be accepted by each other. Armada Riyanto's philosophy of relationality centers on the idea that humans are essentially relational beings. In addition, Riyanto uses four key concepts to explain his philosophy of relationality: I, Text, Other, and Phenomenon. In the context of religious plurality in Indonesia, dialogal relationality plays an important role in building effective and harmonious communication between religious communities because it emphasizes the importance of intersubjective relations that prioritize equality and openness in human interactions.